THE ROLE OF METACOGNITION IN LEARNING AND TEACHING OF PHYSICS - Rajkumar, S. (SCHOOL SCIENCE, 2010)
This article provides a brief overview of the theory of metacognition and its role in learning and teaching. The metacognitive knowledge of strategy, task and personal variables enables students to perform better and learn more. The instructional strategies that facilitate the construction of knowledge are discussed. Metacognitive strategies for physics learning and teaching are given.